2010
DOI: 10.1016/j.lungcan.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator gene mutation and lung cancer risk

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) holds an important role in retaining lung function, but its association with lung cancer is unclear. A case-control study was conducted to determine the possible associations of the genetic variants in the CFTR gene with lung cancer risk. Genotypes of a most common deletion ΔF508, one functional SNP, and eight tag SNPs in the CFTR gene were determined in 574 lung cancer patients and 679 controls. A logistic regression model, adjusting for known ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…5 Dysregulation of the CFTR gene is involved in several human diseases, including cystic fibrosis (CF), in which the gene is defective. 6 Genetic variations in the CFTR gene may also influence the risk of developing a variety of cancers, 7,8 suggesting that the gene may function as a tumor suppressor or promoter, according to the type of tumor. A recent study in CF lung disease showed that CFTR dysfunction can also lead to activation of epithelial cell signaling pathways and subsequent hyperinflammatory responses mediated by nuclear factor JB (NF-JB).…”
mentioning
confidence: 99%
“…5 Dysregulation of the CFTR gene is involved in several human diseases, including cystic fibrosis (CF), in which the gene is defective. 6 Genetic variations in the CFTR gene may also influence the risk of developing a variety of cancers, 7,8 suggesting that the gene may function as a tumor suppressor or promoter, according to the type of tumor. A recent study in CF lung disease showed that CFTR dysfunction can also lead to activation of epithelial cell signaling pathways and subsequent hyperinflammatory responses mediated by nuclear factor JB (NF-JB).…”
mentioning
confidence: 99%
“…The study comprised of 385 men, reported a 92% specificity, for overall prostate cancer, in contrast to 65% for PSA [6,8,12,17,18]. After a thorough examination of the methods was performed, the assays show technical inadequacies and discrepancies.…”
Section: Pitfall 3: Inadequate Experimental Resultsmentioning
confidence: 99%
“…In particular, the example in the first pitfall can be rephrased such that many protein biomarkers are not cancer specific; that is, conditions other than the disease itself, may cause a protein biomarker to be present or be at an elevated level. In addition, the levels of some protein biomarkers are not elevated in all patients with a particular cancer [18]. Therefore, the computational assessment is an important tool to validate the quality of the biomarker.…”
Section: Pitfall 3: Inadequate Experimental Resultsmentioning
confidence: 99%
“…Genetic variations in CFTR may be associated with increased or decreased risk for developing cancers, [44][45][46] suggesting that CFTR is a tumor suppressor or promoter, according to the type of tumor. The high level of CFTR expression is associated with tumor malignancy, progression in ovarian cancer and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%